A case-control study of benign ovarian tumours. Issue 5 (October 1992) - Booth, M; Beral, V; Maconochie, N; Carpenter, L; Scott, C
Abstract : STUDY OBJECTIVE–The aim was to investigate the association between reproductive, contraceptive, and menstrual factors and risk of benign ovarian tumours. DESIGN AND SETTING–This was a case-control study carried out in six London Hospitals. An interviewer administered questionnaire was used. SUBJECTS–62 women with a benign epithelial ovarian neoplasm, 37 women with a functional ovarian cyst, and 20 women with a dermoid cyst presenting between 1983 and 1985, together with 132 controls, took part in the study. MAIN RESULTS–On average, women with a benign epithelial ovarian neoplasm were older than those with a functional ovarian cyst, who in turn were older than those with a dermoid cyst. Nulliparity and infertility were associated with an increased risk, and multiparity with a reduced risk, of benign epithelial ovarian neoplasms. Infertility and pelvic inflammatory disease were associated with increased risks of functional and dermoid cysts. Recent use of oral contraceptives was associated with a reduced risk of all three tumour types. CONCLUSIONS–The findings suggest that the aetiology of ovarian cysts and benign epithelial ovarian neoplasms may differ. The aetiology of benign and malignant epithelial ovarian neoplasms may be similar, however, since some risk factors are shared.